1994
DOI: 10.1177/000348949410300907
|View full text |Cite
|
Sign up to set email alerts
|

Sarcomas of the Nasal Cavity and Paranasal Sinuses

Abstract: Sarcomas of the nose and paranasal sinuses are rare malignancies. Key issues remain unresolved in the management of these tumors, particularly with regard to the role of radiotherapy. To help clarify these issues, 48 consecutive cases of nasal and paranasal sinus sarcomas treated at the University of California, Los Angeles, between 1958 and 1988 were retrospectively reviewed. Six of 16 patients managed initially with surgery alone were cured. All had negative surgical margins and 5 of the 6 had low-grade tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 20 publications
2
39
0
2
Order By: Relevance
“…Lack of early clinical symptoms of sarcomas originating in the nasal cavity and paranasal sinuses, in addition to the proximity and extension into the meninges and skull base contribute to poor prognosis. More aggressive and poorly differentiated lesions usually present only after invasion of adjacent structures, such as the orbit, cribriform plate, and brain [9]. Such was the case in our patient who developed OAS characterized by multiple cranial neuropathies without evidence of nasal or sinus features.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Lack of early clinical symptoms of sarcomas originating in the nasal cavity and paranasal sinuses, in addition to the proximity and extension into the meninges and skull base contribute to poor prognosis. More aggressive and poorly differentiated lesions usually present only after invasion of adjacent structures, such as the orbit, cribriform plate, and brain [9]. Such was the case in our patient who developed OAS characterized by multiple cranial neuropathies without evidence of nasal or sinus features.…”
Section: Discussionsupporting
confidence: 55%
“…Paranasal sinus RMS commonly produces symptoms and signs of nasal obstruction, discharge, bleeding, pain, and swelling, which may be mistaken for those of inflammatory conditions as acute or chronic sinusitis. Less commonly, paranasal sinus masses may manifest as proptosis, optic neuropathy, hyperemia of the eye, epiphora, toothache, or headache [8,9]. Lack of early clinical symptoms of sarcomas originating in the nasal cavity and paranasal sinuses, in addition to the proximity and extension into the meninges and skull base contribute to poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Early tumors typically produce localized nasal symptoms. Rhabdomyosarcoma is no exception; nasal obstruction, rhinorrhea, and recurrent otitis media are the most common presenting symptoms [6]. Persistent pain, sero-sanguineous discharge or cranial nerve palsies eventually indicate the serious cause of the symptoms, the tumor often attaining a fairly large size at initial diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Sercarz et al [109] recommended radiotherapy in sinonasal sarcomas at least when positive surgical margins are present. Callender et al [110] showed, in an excellent study including 37 adult and pediatric patients with rhabdomyosarcoma of the paranasal sinuses, that chemotherapy and radiotherapy, eventually with surgery after chemoradiotherapy, might provide the best means of obtaining locoregional control.…”
Section: Treatment For Sinonasal Sarcomasmentioning
confidence: 99%